Efetividade de um programa educacional voltado para a prática de atividade física em pacientes com insuficiência renal crônica em hemodiálise - Hashimoto, Raquel de Fátima Cavalheiro (2014)
Introduction: Chronic renal failure patients on dialysis program are generally sedentary. Among several possible causes for this we highlight the lack of information and stimulus for increase physical activity. This inactivity is related to decreased quality of life. Objective: To determine the intensity of physical activity and evaluate the response, in hemodialysis patients, to orientation and education aimed to increase this activity. Methodology. The study was conducted at the Center for Dialysis and Renal Transplantation, Hospital Santa Lucinda, PUC/SP. It was studied the influence of an educational theoretical and practice program developed to encourage physical activity in 14 hemodialysis patients. Educational activities were consisted of a short theoretical introduction followed by collective exercises and was held during four months in 2013. To evaluate the program itself and the participation of patients, we used the International Questionnaire on Physical Activity (long version IPAQ, 2012), a record on the average minutes of daily walking and collective gymnastic time and specific questions about the validity of the course. Quality of life before and after the course was evaluated by the Kidney Disease Questionnaire-Quality of Life (KDQOL- SFTM13). Results: The patients increased significantly the practice of walking on the day out of hemodialysis (8.3; 6.0; 23.8 and 24.8 min respectively in the first, second, third and fourth month of the educational program; p <0.001 between the last two months versus the first two months) and completed all collective practices. 10 patients improved the level of their classification of physical activity and all patients made a positive evaluation of the educational program. The comparison pre and post program of the answers to the KDQOL questionnaire showed a significantly improvement in several domains after the educational program. The practice of collective exercises did not induce any clinical complication. Conclusions: The educational program induced an increase in physical activity, an improvement of quality of life, was safe and well evaluated by hemodialysis patients